Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1350/ijps.6.3.155.39131
|View full text |Cite
|
Sign up to set email alerts
|

Crime Victims' Experiences of Police Interviews and Their Inclination to Provide or Omit Information

Abstract: Ulf Holmberg is a veteran police officer of 30 years' service in Sweden. He has worked in a number of different departments, including spending 15 years as an investigator of violent and sexual crimes. He has recently been awarded his PhD. ABSTRACT This research concerns crime victims' experiences ofSwedish police interviews and their inclination to provide or omit information in such interviews. A group of rape or aggravated assault victims, consisting of 178 women and men, answered a questionnaire in this ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 13 publications
(17 reference statements)
4
36
0
Order By: Relevance
“…This corresponds with other research on the Utøya investigative interviews which described different ways the police interviewers showed support to the victims during the interview (Jakobsen et al, 2016), and, how factors like empathic police officers and being able to provide a coherent narrative contributed to a positive interview experience (Langballe & Schultz, 2017). Even though empathy has not been clearly defined in investigative interviewing (Oxburgh & Ost, 2011), which makes it challenging to know when it is occurring, it is still considered important for the development of rapport (Dando & Oxburgh, 2016;Holmberg, 2004a;Madsen & Holmberg, 2015;Vanderhallen & Vervaeke, 2014).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This corresponds with other research on the Utøya investigative interviews which described different ways the police interviewers showed support to the victims during the interview (Jakobsen et al, 2016), and, how factors like empathic police officers and being able to provide a coherent narrative contributed to a positive interview experience (Langballe & Schultz, 2017). Even though empathy has not been clearly defined in investigative interviewing (Oxburgh & Ost, 2011), which makes it challenging to know when it is occurring, it is still considered important for the development of rapport (Dando & Oxburgh, 2016;Holmberg, 2004a;Madsen & Holmberg, 2015;Vanderhallen & Vervaeke, 2014).…”
Section: Discussionsupporting
confidence: 84%
“…Holmberg (2004a) examined how victims of rape and aggravated assault perceived the style, attitudes and responses of the police interviewer in their respective investigative interview. The study showed the victims' experience of two police interviewing styles: the dominant and the humanitarian approach.…”
Section: Rapportmentioning
confidence: 99%
“…In their study, Xei et al found that the greater the police efforts following the most recent victimization of an individual, the greater the likelihood that that individual will report subsequent victimization events to the police. Furthermo re, consistent with Hickman and Simpson's [12] and Ho lmberg's [13] research findings, Xei et al 's research shows that a positive police response to prior vict imization (i.e., if the offender who committed the crime against the victim was arrested) encouraged victims to report subsequent crimes to the police. Regarding vicarious reporting of crimes 1 to the police, Xei et al 's research shows that victimization of, fo r example, another household member d id not have an effect on an individual's crime-reporting behavior 2 .…”
Section: The Effect Of Victi Mization Experiences On Crime -Reportingmentioning
confidence: 68%
“…Research shows that victimizat ion experiences have a positive influence on crime-reporting behavior. In this context, emp irical evidence suggests that those who have been previously victimized by crime are mo re likely to report crimes to the police [8,47,48]. Of the two types of victimizations (i.e., crimes against property vs. crimes against persons), as discussed above, research shows that victims of property crimes are more likely to report crimes to the police in general.…”
Section: The Present Studymentioning
confidence: 97%
See 1 more Smart Citation